The role of Bach2 in regulating CD8 + T cell development and function - Xinyu Weng; Min Zheng; Yanning Liu; Guohua Lou (Cell Communication and Signaling, 2024)
Abstract Bach2 was initially discovered in B cells, where it was revealed to control the transcription involved in cell differentiation. Bach2 is intimately connected to CD8 + T lymphocytes in various differentiation states and subsets according to recent findings. Bach2 can regulate primitive T cells, stimulate the development and differentiation of memory CD8 + T cells, inhibit the differentiation of effector CD8 + T cells, and play a significant role in the exhaustion of CD8 + T cells. The appearance and development of diseases are tightly linked to irregular CD8 + T cell differentiation and function. Accordingly, Bach2 offers novel approaches and possible targets for the clinical treatment of associated disorders based on research on these pathways. Here, we summarize the role of Bach2 in the function and differentiation of CD8 + T cells and its potential clinical applications.